ОБРАЗ «ЧЕРНОБЫЛЬСКОГО ЧЕЛОВЕКА» В ЧЕРНОБЫЛЬСКОЙ МОЛИТВЕ СВЕТЛАНЫ АЛЕКСИЕВИЧ - Słupianek-Tajnert, Daria (Acta Neophilologica, 2019)
This article is an attempt at recreating the portrait of a “Chernobyl Man” created by Svetlana Alexievich in Chernobyl Prayer. The “Chernobyl Man” is a certain psychological type whose psychological portrait is drawn based on their entanglement in the current social and political realities. On the one hand, the “Chernobyl Man” is a typical representative of a homo sovieticus – an individual displaying boundless devotion to the state. On the other hand, this type of man through their relationship with the world is living proof of the spiritual disintegration of the Soviet empire.